The Concept of the Learning Organization in Malaysia: A Reinterpretation Exercise? - Brouckmans, Petra (2007)
The landscape in which current organizations operate is characterized by continual and disruptive change (Kotter and Cohen, 2002, in Thomas and Allen, 2006). To remain relevant and competitive, organizations need to consciously adapt and transform through a process of learning at all levels of the organization (Senge, 1995). The concept of the learning organization transpired around 1990, influenced by writers such as Senge (1990) in the USA and Pedlar et al. (1991) in the UK (in He-Chuan Sun, 2003). Since its emergence, the concept has proven to be powerful and persuasive and many organizations have embarked on the journey to become closer to this idea(l). In Asia, the concept has been adopted in numerous countries and some Asian researchers have applied this concept whilst looking at their firms. Most of this research does not reflect on the applicability of the concept of the learning organization in Asian cultures. There is an assumption that this concept, which is largely developed by Western business gurus from individualist and low power distance cultures, can be easily transferred to collectivist and high power distance societies. This study looks at how the concept is currently being applied in a Malaysian national context. It examines the barriers and enablers that Malaysian culture poses to implementing this concept and considers to what extent the concept needs to be adapted in an Asian environment. For this purpose, the case study methodology was used to examine seven organizations (6 multinationals and one Malaysian organization) operating in Malaysia. The findings indicate that though Malaysian high-distance culture and Malay uncertainty avoidance do have an inhibiting impact on increasing the learning capability of organizations; the Malaysian collectivist and Malay feminine cultural components have the potential to contribute positively to the implementation of this concept in Malaysia. This research also summarizes the key differences found between the multinationals operating in Malaysia and the Malaysian organization. The study proposes that several Malaysian organizations may not be ready to become learning organizations. The concept of the training organization is suggested to offer a more realistic and achievable transitional objective for these organizations.